Kajian Dampak Bank Sampah Terhadap Perbaikan Lingkungan Negeri Hatu Maluku Tengah - Aisyah Hadi Ramadani; Mohammad Taufik; Siti Fatonah (Universitas Nusantara PGRI Kediri, 2020)
Negeri Hatu is an area at the level of a village or sub-district located in Central Maluku Regency, Maluku Province. Negeri Hatu is located far from the city center and the center of the Maluku Tengah regency government, resulting in no reach of waste management services from the local DLH. The absence of waste management facilities in this area was reinforced by the lack of public awareness about environmental cleanliness which triggered the idea of ​​establishing a waste bank by the manager of the Hasoma smart home. The waste bank that was established was an implementation of environmental literacy to the community in Hatu Country. The waste bank has had a significant impact on environmental change and the improvement of the community's economy. However, this needs to be studied further in accordance with the context of the character of the community in each region. The purpose of this study was to evaluate the effectiveness of environmental literacy through waste banks and to analyze the potential of waste banks in improving environmental quality in Hatu Country. The research was conducted with a qualitative descriptive approach where data were taken from in-depth interviews and analyzed to obtain a value for the effectiveness of the activity. The results showed that the environmental literacy practice implemented by the Hasoma smart house was able to open people's environmental insight in terms of the impact of waste on health, the importance of sorting waste according to its type and increasing participation in caring for environmental cleanliness. Waste banks are able to reduce domestic waste generation by 0.17% in Hatu Country and are able to reduce carbon emissions by 2702.35 gCO per month. The activities of the waste bank at Hasoma Hatu's smart home can change the social community in Negeri Hatu. This change can be seen from the high participation of the younger generation in the initial weighing of the waste bank.